Tahapan Perkembangan Kognitif Siswa Berdasarkan Teori Piaget Serta Peran Guru dalam Mendukungnya - Landung Prasetyo; Luki Eka ferdian (CV. ITTC INDONESIA, 2024)
Development is a process of physical and psychological change that reflects an increase in complexity from a simple state to a more complex state and occurs regularly and systematically throughout an individual's lifetime. For students, development includes not only the need for guidance and independent abilities, but also unique physical and psychological growth. This article describes the stages of student development which include the sensorimotor stage, preoperational stage, concrete operational stage, and formal operational stage, based on Jean Piaget's theory. Apart from that, internal and external factors that influence student development are also identified, including physical, psychological, family, school and community environmental factors. Educators play an important role in supporting student development through various strategies, including: Building skills, providing motivation, and creating an environment conducive to learning. With the right approach, optimal student development can be achieved.